Technology Transfer Through Company Takeovers by Chinese Investors - Jürgen Matthes (Wirtschaftsdienst)
Abstract The usual positive effects of foreign investments are only valid to a limited extent for company takeovers by Chinese investors. Moreover, there are numerous indications that such take-overs aim for a transfer of technology for industrial policy reasons. This favours China’s rapid technological catch-up, which could lead to a loss of prosperity in the industrialised countries, as is suggested by relevant trade models whose assumptions do not appear unrealistic on closer examination. Such concerns are exacerbated by the continuing competitive distortions of Chinese state capitalism. Therefore, tighter restrictions on corporate takeovers appear appropriate for reasons, but should be handled with restraint.